Antioxidants and Calcium Modulators Preclude in Vitro Hepatitis B Virus–Induced Mitochondrial Damage - Jabeen, Kehkshan; Javed, Aneela; Manzoor, Sobia; Shahzad, Shaheen (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Hepatitis B virus induces mitochondrial damage via the production of reactive oxygen species and concomitant with deregulation of calcium homeostasis. The current study evaluates the potential of antioxidant and calcium modulators for inhibition of hepatitis B virus-induced mitochondrial damage using in vitro cell culture models. Materials and Methods: Hepatitis B virus-induced mitochondrial fragmentation was observed by immunofluorescence confocal micros- copy in hepatitis B virus-infected cell lines (HepG2 and HepAD38). Differential protein expression of mitochondrial fragmentation mark- ers, dynamin-related protein 1 and phospho-dynamin-related protein 1, were evaluated both pre- and posttreatment with antioxidant N-acetyl-l-cysteine and calcium modulators like 1,2-bis(2-aminophenoxy)ethane-N,N,N′,N′-tetraacetic acid tetrakisacetoxymethyl ester, ethylene-bis (oxyethylenenitrilo) tetraacetic acid glycol ether diamine tetraacetic acid-acetoxymethyl ester, and ruthenium amine complex by western blot analysis. Results: A slight reduction in mitochondrial fragmentation in both cell lines was observed post-antioxidant treatment with a partial prevention observed with calcium modulators. The expression of phospho-dynamin-related protein 1 was significantly upregulated (P = .0007, P = .003) in both hepatitis B virus-infected cell lines compared to uninfected cells. In line with these observations, the expres- sion of dynamin-related protein 1 and phospho-dynamin-related protein 1 was found to be significantly downregulated with N-acetyl- l-cysteine treatment in both cell lines (P = .003, P = .002), respectively. A nonsignificant trend was observed in the case of calcium modulators treatment. Conclusions: Current study indicates that the mitochondrial fragmentation induced by hepatitis B virus infection can be reduced after antioxidant treatment pointing toward exploring better drug targets for the prevention of hepatitis B virus-induced mitochondrial frag- mentation and associated liver damage. Cite this article as: Jabeen K, Javed A, Manzoor S, Shahzad S. Antioxidants and calcium modulators preclude in vitro hepatitis B virus–induced mitochondrial damage. Turk J Gastroenterol. 2023;34(10):1052-1061.